Turning The Challenge Of Recession Into An Opportunity With Islamic Economics - Rafi Siregar, Muhammad (LP2M IAIN Palopo, 2024)
This research aims to explore the role of sharia economics in turning recession challenges into opportunities in Indonesia. The research method used is a mixed approach that combines quantitative and qualitative methods. The exploration phase involves an in-depth literature study of the principles of sharia economics, analysis of successful cases from other countries, and interviews with stakeholders in Indonesia. The analysis phase includes the collection of macroeconomic and microeconomic data, as well as qualitative data through in-depth interviews and focused group discussions. The results of the study show that the sharia economy makes a significant contribution to Indonesia's economic growth in recession conditions. The implementation of sharia economic principles, such as the prohibition of riba and the practice of gharar, has the potential to increase economic stability by encouraging investment oriented towards the real and sustainable economy. The use of zakat and waqf in the sharia economy has also proven to be effective in reducing socio-economic inequality and increasing a fairer distribution of income. The conclusion of this study emphasizes the importance of strengthening Islamic financial infrastructure, increasing Islamic financial literacy in the community, and strengthening cooperation between the public and private sectors in supporting Islamic economic growth. Challenges that need to be addressed include a clearer regulatory framework and strong policy support to expand the penetration of the sharia economy in key sectors. With the right implementation of recommendations, the sharia economy can play an important role in building sustainable economic stability and prosperity in Indonesia, as well as make a significant contribution to effectively overcoming the economic recession